2020
DOI: 10.1017/s0272263120000261
|View full text |Cite
|
Sign up to set email alerts
|

On the Scope of Output in Sla

Abstract: Following calls for more modality-sensitive perspectives of SLA, this study investigated the extent to which (a) producing the second language (L2) in the oral modality impacts learner-generated noticing and L2 development of grammatical structures embedded in subsequent auditory input, and whether (b) engaging in L2 production and input processing in the written modality differentially contributes to learner noticing and L2 outcomes compared to the oral modality. Participants were beginner-level L2 Spanish le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In relation to aspectual production and task, previous studies that employed tasks that allow learners planning time are generally supportive of the AH (Ramsay, 1990;Hasbun, 1995), while studies that involve very little to no planning time support either the AH (Camps, 2002(Camps, , 2005 or the DPTH (Salaberry, 1999(Salaberry, , 2002. The most relevant in this respect is a study by Bardovi-Harlig (1998), which directly compared oral and written narratives of intermediate-level classroom L2 learners of English to assess the effect of task modality (Gilabert et al, 2016;Zalbidea, 2021). The results supported the associative predictions of the AH in both modalities.…”
Section: The Default Past Tense Hypothesismentioning
confidence: 99%
“…In relation to aspectual production and task, previous studies that employed tasks that allow learners planning time are generally supportive of the AH (Ramsay, 1990;Hasbun, 1995), while studies that involve very little to no planning time support either the AH (Camps, 2002(Camps, , 2005 or the DPTH (Salaberry, 1999(Salaberry, , 2002. The most relevant in this respect is a study by Bardovi-Harlig (1998), which directly compared oral and written narratives of intermediate-level classroom L2 learners of English to assess the effect of task modality (Gilabert et al, 2016;Zalbidea, 2021). The results supported the associative predictions of the AH in both modalities.…”
Section: The Default Past Tense Hypothesismentioning
confidence: 99%
“…This contrasts with previous research in several important ways. Firstly, previous research on FL vocabulary with secondary-school learners did not find a lag effect using other types of tasks (Küpper-Tetzel et al, 2014;Rogers & Cheung, 2020, 2021Serrano & Huang, 2018, 2021. Secondly, previous lab studies have only found an advantage to a longer vocabulary learning through Quizlet.…”
Section: Discussionmentioning
confidence: 89%
“…The excerpt confirms some features of behaviorism in L2 acquisition. From the dataset, reading skills or oral discourses are essential to learn Philippine English (Estremera, 2018;Zalbidea, 2021). In truth, stimulusresponse as one of the features of behaviorism has paved the way for the grammatical competence and reading prowess of the participants.…”
Section: Features Of Behaviorismmentioning
confidence: 99%